DEC-205 is a cell surface receptor for CpG oligonucleotides - Lahoud, Mireille H. (National Academy of Sciences, 2012)
Synthetic CpG oligonucleotides (ODN) have potent immunostimulatory properties exploited in clinical vaccine trials. How CpG ODN are captured and delivered to the intracellular receptor TLR9, however, has been elusive. Here we show that DEC-205, a multilectin receptor expressed by a variety of cells, is a receptor for CpG ODN. When CpG ODN are used as an adjuvant, mice deficient in DEC-205 have impaired dendritic cell (DC) and B-cell maturation, are unable to make some cytokines such as IL-12, and display suboptimal cytotoxic T-cell responses. We reveal that DEC-205 directly binds class B CpG ODN and enhances their uptake. The CpG-ODN binding function of DEC-205 is conserved between mouse and man, although human DEC-205 preferentially binds a specific class B CpG ODN that has been selected for human clinical trials. Our findings identify an important receptor for class B CpG ODN and reveal a unique function for DEC-205.